Kajian Rekayasa Lalu Lintas Simpang Tiga Narmada Menggunakan Software PTV VISSIM - Ritiya Ariyani; Anwar Efendy; Adiman Fariyadin (Institut Teknologi Garut, 2026)
The increase in population and vehicle numbers in West Lombok Regency has caused a decline in traffic performance, particularly at the Narmada Three-Legged Intersection, which has high commercial activity and side friction. This study aims to evaluate the existing intersection performance and analyze the effectiveness of traffic engineering measures in the form of road widening and the implementation of traffic signals (APILL). Data were obtained through geometric and traffic volume surveys conducted over three days at 15-minute intervals, then analyzed using PKJI 2023 and PTV Vissim simulation. The analysis results show that the existing intersection condition has a capacity of 3,453 passenger car units per hour (pcu/hour), a degree of saturation of 0.76, an average delay of 14.99 seconds, and a Level of Service category B. The scenario of widening the road by 2 meters on each intersection approach was able to increase capacity to 3,730 pcu/hour while reducing the degree of saturation and delay, thereby improving intersection performance. In contrast, the implementation of a three-phase traffic signal increased delay and queue length, with simulation results even showing a decline in Level of Service to category F. Based on the research findings, the most effective solution for improving the performance of the Narmada Three-Legged Intersection is road widening by 2 meters without implementing traffic signals.